Assessment of the Potential of Sodium Benzoate as Anti-Microbial and Anti-Corrosion Agent in Coolant - Wong, Leong Seng; Wong, Siong Ding; Liang, William; Chin, Clarence; Sim, Siong Fong (Science & Technology Asia, 2025)
Sodium benzoate, as both an antimicrobial agent and corrosion inhibitor, is ideally suited for application in engine coolant. This study evaluated the antimicrobial and anticorrosion properties of sodium benzoate in an ethylene glycol-based organic engine coolant. Antimicrobial assays tested sodium benzoate against Bacillus cereus, Pseudomonas aeruginosa, and Trichoderma viviens. The corrosion inhibitory effect was assessed using the ASTM D1384 glassware corrosion test. It was found that 3% wt sodium benzoate strongly inhibited microbial growth, while a minimum dosage of 1% wt provided only mild antimicrobial performance. Interestingly, the presence of 50% ethylene glycol in the coolant outperformed sodium benzoate in antimicrobial effectiveness. Sodium benzoate also exhibited selective corrosion protection; at a dosage of 1% wt, it offered superior protection for aluminum but promoted corrosion of iron.